Kuratowski-Zorn lemma in High Scholl mathematics (Research, Society and Development, 2021)
Zorn's lemma has been the subject of controversy and debate since its emergence, despite its relevance can be perceived by the large number of applications and consequences presented on the form of equivalent statements that are present in the area of ​​exact, and also in mathematical applications that they are based on the set theory as, axiom of Choice, Theorem of Good Order, Tychonoff's Theorem, Hahn Banach Theorem among others, the first three being equivalent to Zorn's Lemma. For this reason, we will aim, starting from a historical approach on the same, to present one of the applications that are responsible for strengthening its notoriety and popularity among mathematical scholars and scientists from the most varied areas that use Linear Algebra to represent and solve their problems. mathematical models using this lemma and its equivalences, where we will see how we can find it in the mathematics of regular high school schools when presented to students.